2019
DOI: 10.1002/ijop.12646
|View full text |Cite
|
Sign up to set email alerts
|

Dysmorphic concern and behavioural impairment related to body image in adolescents

Abstract: This study examined a moderated mediation model testing whether dysmorphic concern is related to behaviour altered to change appearance. This relationship is potentially mediated by depressive symptomatology (dysphoria and self‐esteem) and ideas of reference about “laughing, commenting” and “attention, appearance,” and each mediated relationship moderated by sex. The sample was made up of 3377 adolescents from 12 to 18 years old (Mage = 14.52; SD = 1.65, 56.5% girls). The results showed that dysphoria and idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 32 publications
2
15
1
Order By: Relevance
“…Although the attention and appearance IR were related to the use of Instagram, the relationship with DC was not statistically significant, even though the correlational analyses showed a significant relationship. These results do not back the findings of Senín-Calderón et al (2019) in a sample of adolescents. It is possible that ER difficulties and appearance-related comparison are more relevant in the relationship with DC and may have diminished the importance of attention and appearance IR to the point of not being included in the model.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Although the attention and appearance IR were related to the use of Instagram, the relationship with DC was not statistically significant, even though the correlational analyses showed a significant relationship. These results do not back the findings of Senín-Calderón et al (2019) in a sample of adolescents. It is possible that ER difficulties and appearance-related comparison are more relevant in the relationship with DC and may have diminished the importance of attention and appearance IR to the point of not being included in the model.…”
Section: Discussioncontrasting
confidence: 99%
“… Phillips (2004) found that at least two thirds of BDD patients experienced IR. Senín-Calderón et al (2019) found that IR about “attention, appearance” and “laughing, commenting” mediated the relationship between DC and behavioral impairment related to body image in adolescents. In another study, IR mediated the relationship between concern for appearance and behavioral impairment related to body image ( Senín-Calderón, Rodríguez-Testal, Perona-Garcelán, & Perpiñá, 2017 ).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…The potential impact of the closure of beauty services could be worse for individuals with "dysmorphic concern," a preoccupation with a perceived defect in physical appearance (Oosthuizen, Lambert, & Castle, 1998). This commonly occurs in body image disorders, such as eating disorders and body dysmorphic disorder (BDD), where individuals may overestimate their body weight or size, or the extent of a flaw in their appearance (Beilharz et al, 2019;Phillipou et al, 2016;Schieber, Kollei, de Zwaan, & Martin, 2018). For these individuals, the seeking of beauty treatments can act as a safety behavior, which assists in relieving appearance-related anxiety in the short-term but may perpetuate an excessive focus on appearance in the long-term (Wilhelm, Phillips, & Steketee, 2013).…”
mentioning
confidence: 99%